We all need help: "Big Data" and the mismeasure of public administration - Lavertu, Stephane (2016)
Rapid advances in our ability to collect, analyze, and disseminate information are transforming public administration. This big data revolution presents opportunities for improving the management of public programs, but it also entails some risks. In addition to potentially magnifying well-known problems with public sector performance managementparticularly the problem of goal displacementthe widespread dissemination of administrative data and performance information increasingly enables external political actors to peer into and evaluate the administration of public programs. The latter trend is consequential because external actors may have little sense of the validity of performance metrics and little understanding of the policy priorities they capture. The author illustrates these potential problems using recent research on U.S. primary and secondary education and suggests that public administration scholars could help improve governance in the data-rich future by informing the development and dissemination of organizational report cards that better capture the value that public agencies deliver. - Reproduced.
Keywords: Public administration